Factors impacting the height of the interproximal papilla: A cross‐sectional study - Hamdane Khaireddine; Tlili Mohamed; Rmida Arij; Khanfir Faten; Ben Amor Faten (Wiley, 2023)
Abstract Objectives To determine the relationship between different parameters (age, periodontal phenotype, contact point height, and crown shape) and the height of the interproximal papilla around the teeth of/in the maxillary anterior sector. Material and Methods A total of 45 subjects were involved in this study, with 315 interproximal papillae of the maxillary anterior sector. The interproximal papillae were clinically classified according to the Norland and Tarnow classification. The periodontal phenotype was assessed by periodontal probe transparency through the marginal gingiva. The height of the papilla, the height of the contact points, and the width/length ratio of the crown were also measured using the periodontal probe. The relationship between the variables was studied using Pearson's correlation. Statistical significance was set at a value of p < .05. Results A positive correlation was found between age and the papilla score. However, a negative correlation was noted between age and papilla height, with statistically significant values. A negative correlation was found between the papilla score and the rest of the studied clinical parameters. However, this correlation was not found with regard to the height of the papilla with the same parameters, except for the height of the contact points. Conclusions A statistically significant relationship was noted between the appearance of the interproximal papillae and all the parameters studied.